Analytical solutions of geohydrological problems - Bruggeman, G. A. (Developments in water science ;, 1999)
This book has been divided into two parts, A and B. Part A comprises analytical solutions of about 1100 geohydrological problems in the saturated zone. Classification of the problems according to certain characteristics. Part B consists of three chapters, describing the basic principles for saturated ground water flow, analytical solution methods and mathematical functions respectively.